THE ROLE ANALYSIS OF INDONESIA'S POLICY STRATEGY ON INDO-PACIFIC - Aisyah Dwi (UIR Press, 2020)
The emergence of Indo-Pacific terminology which is increasingly developing causes the interest of countries to be involved in the role of the region increasingly high for various reasons. Indonesia as an archipelagic country has the opportunity to improve its strategic position to support of the